Assessment of Financial Literacy and Its Impact on Investor’s Decisions in Saudi Arabia: A Study in the Context of Enabling Financial Planning to Strengthen Economic Development - Amar Johri; Misbah Ul Islam; Mustafa Kamal (Discrete Dynamics in Nature and Society)
The significance of financial literacy is increasing faster in today’s world. Financial literacy provides individuals with necessary and adequate financial knowledge and makes them professionally aware of managing their finances. It plays a vital role in the economic development of an economy. The study examines the impact of financial literacy on investors’ financial decisions, financial planning, selection of financial products, and financial literacy awareness program and its influence on investors’ investment decisions. In order to obtain information from the respondents, we employed a questionnaire that was both structured and self-administered. The investigation analyzes the survey responses from 360 respondents in Saudi Arabia. Various statistical methods such as descriptive statistics, correlation analysis, analysis of reliability, analysis of variance (ANOVA), and regression analysis were utilized to evaluate the data obtained. The results obtained in the study indicated that financial literacy has a significant impact on investors’ financial decisions, financial planning, and the selection of financial products that influence investors’ investment decisions. The research also found that financial literacy is affected by financial literacy awareness programs, which have a favorable influence on the investment decisions made by investors. The study’s findings will help prospective investors understand the importance of raising financial knowledge for their future financial goals.